Hubungan antara hasil tes kebugaran jasmani dengan hasil belajar semester gasal - Pratama, Reza Wahyu; Nurrochmah, Siti (Jurnal Porkes, 2023)
Due to the Covid-19 pandemic, online practical learning is considered inadequate, posing a number of challenges in the learning process. This review aims to determine the information and relationship between actual health status and odd semester learning outcomes among students of the class of 2021 in the Actual Education, welfare and diversion branch. With a population/sample of 84 randomly selected students, observation was used to collect data. The test instrument used TKJI test instruments and non-tests, for special documentation. The single correlation test is an inferential statistic used in the data analysis method. The results obtained are the R^2 value of 0.443 in the men's group and 0.447 in the women's group, so there is a relationship between actual health and odd semester learning outcomes in students of batches A and C of 2021 Actual School of Welfare and Entertainment, State College of Malang. it is concluded that there is a significant correlation between the level of physical fitness and learning achievement, especially in the male student group by contributing to the learning outcomes which are quite large and for the female group contributing to learning outcomes.